Improved efficiency in automated acquisition of ultra-high-resolution electron holograms using automated target detection. (25th June 2021) - Ichihashi, Fumiaki; Tanigaki, Toshiaki; Akashi, Tetsuya; Takahashi, Yoshio; Kusada, Kohei; Tamaoka, Takehiro; Kitagawa, Hiroshi; Shinada, Hiroyuki; Murakami, Yasukazu
Abstract: An automated hologram acquisition system for big-data analysis and for improving the statistical precision of phase analysis has been upgraded with automated particle detection technology. The coordinates of objects in low-magnification images are automatically detected using zero-mean normalized cross-correlation with preselected reference images. In contrast with the conventional scanning acquisitions from the whole area of a microgrid and/or a thin specimen, the new method allows efficient data collections only from the desired fields of view including the particles. The acquisition time of the cubic/triangular nanoparticles that were observed was shortened by about one-fifty eighth that of the conventional scanning acquisition method because of efficient data collections. The developed technology can improve statistical precision in electron holography with shorter acquisition time and is applicable to the analysis of electromagnetic fields for various kinds of nanoparticles.